Analysis of Verbstellung Errors in A2-B1 German Language Students' Podcast Assignments in the Mündliche Kommunikation Course - Pratiwi, Anin Saufa; Amalia, Raida Zharfa; Sobara, Iwa (Proceeding of International Conference on Education, Language, Literacies, and Literary Studies (ICONELS), 2025)
This study aims to analyze Verbstellung (verb order) errors in German verbal communication made by A2-B1 level students through podcast assignments in the Mündliche Kommunikation course. The analysis was conducted using Pit Corder's error analysis theory approach, which provided the researcher with the opportunity to identify the types and characteristics of the errors. Verbstellung is an important aspect of German sentence structure that is often a source of errors due to mother tongue interference and lack of understanding of grammatical structures. Data was collected from the transcription of student podcasts, then analyzed to find the dominant error patterns. This study found that verb position errors, especially in subordinate clauses, are a major challenge for beginner learners. Most of the errors indicate that learners do not fully understand German sentence structure, so a teaching approach that focuses more on practice and error correction is needed.